Haptic touch to improve motor skills and sense of touch of stroke patients - Chow, Tec Soon (2020)
This project applies Haptic Technology in medical field. Stroke is the problem targeted in this project. Various stroke rehabilitation exercises exist, but effective rehabilitation exercises are still being researched. Haptic technology is being researched in this project to determine its effectives in helping stroke patients to rehabilitate. This project aims to improve stroke rehabilitation by utilising haptic touch device. The haptic device used in this project is Phantom Omni by 3D Systems. Unity game engine is used to develop the applications in this project. The applications in this project will test skills such as hand-eye-coordination, wrist flexion and wrist extension. The first application is designed for stroke patients to draw straight lines. Haptic effects are there to help stroke patients draw straight lines by pushing their stylus back on track. The second application is similar to first application. Instead of straight lines, spiral lines are to be drawn. The third and fourth application tests the strength of wrist flexion and wrist extension. Stroke patients have go against the haptic force with different levels of strength. The goal is to being able to go against the haptic force that a normal human can. All of these applications are tested on its effectiveness by having stroke patients using it.